2017
DOI: 10.1038/s41598-017-05084-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional determinants of protein assembly into homomeric complexes

Abstract: Approximately half of proteins with experimentally determined structures can interact with other copies of themselves and assemble into homomeric complexes, the overwhelming majority of which (>96%) are symmetric. Although homomerisation is often assumed to a functionally beneficial result of evolutionary selection, there has been little systematic analysis of the relationship between homomer structure and function. Here, utilizing the large numbers of structures and functional annotations now available, we ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…44 There are symmetry arguments for the apparent over-representation of homodimers in the functional protein universe. 45 Thus, we suspect that heterodimerization in NF κ B has been selected by evolution to be the dominant form, thanks to its manifesting a more beneficial trade-off between thermodynamic stability and allosteric functional DNA binding that is needed to allow kinetic control of a large genetic broadcasting network. 7 …”
Section: Resultsmentioning
confidence: 99%
“…44 There are symmetry arguments for the apparent over-representation of homodimers in the functional protein universe. 45 Thus, we suspect that heterodimerization in NF κ B has been selected by evolution to be the dominant form, thanks to its manifesting a more beneficial trade-off between thermodynamic stability and allosteric functional DNA binding that is needed to allow kinetic control of a large genetic broadcasting network. 7 …”
Section: Resultsmentioning
confidence: 99%
“…Our simulated evolution of the duplication of HMs leads to the proposal of a simple mechanism for the maintenance of HET that does not require adaptive mechanisms. A large fraction of HMs and HETs use the same binding interface (Bergendahl and Marsh, 2017) and as a consequence, negative selection on HM interfaces will also preserve HET interfaces. Our results show that mutations have correlated effects on HM and HET, which slows down the evolution of independent complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these hypotheses imply that the retention of paralogs after duplication is more likely for HM proteins due to the enhanced probability of gain of functions. For example, symmetrical HM proteins could have key advantages over monomeric ones for protein stability and regulation (André et al, 2008;Bergendahl and Marsh, 2017). Levy and Teichmann (Levy and Teichmann, 2013) suggested that the duplication of HM proteins serves as a seed for the growth of protein complexes that allow their diversification by creating asymmetry in the complexes and the recruitment of other proteins, leading to their specialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7C). In addition, a relevant study showed that approximately half of the proteins could interact with other copies of themselves and assemble into homomeric complexes, which was often assumed to be a functionally beneficial result of evolutionary selection (11).…”
Section: Evolution Of Nidovirus Endoribonucleasementioning
confidence: 99%